Governance and benefits sharing in the swedish forest commons - Poudyal, Mahesh; Lidestav, Gun (2011)
Unlike forest commons in many other countries, within Europe and elsewhere, Swedish forest commons are for- med and organised in a particular way in that the parcels (or shares) of forestlands involved are privately owned but as commons they are jointly managed by forest pro- fessionals. Furthermore, shares in forest commons are considered as “set asides” of the private landholding (farm/forest) and thus cannot be owned or sold in isolation. This leaves little space for the shareholders to be ‘hands-on’ in the management of these commons, although they are involved in decision making through a management board they elect. Moreover, it has been claimed that the shareholders in the Swedish forest commons do not bear the costs (for management and governance) proportional to the benefits they receive from their commons. In this paper, we use data from a mail survey directed to resident shareholders in three of the major forest com- mons in Sweden (Jokkmokk, Tärna-Stensele, and Älvda- len) to assess their satisfaction on the governance and benefits sharing within their forest commons. This study shows that generally a significant majority of the share- holders in these three forest commons seem to be satis- fied with the status quo regarding the governance/ management of their commons and the benefits they accrue. However, women’s participation in most aspects of the forest commons seems to be significantly lower than their male counterpart leaving them benefiting less from their commons as a result.